PENCIPTAAN KEUNGGULAN BERSAING PERUSAHAAN MELALUI PENINGKATAN PERILAKU PELAYANAN - Hendriyanto, Asepta (STIE Totalwin Semarang, 2013)
The purpose of this research is to investigate and analyze the factors that affect the competitive advantage through service behavior. The method used is the method of survey data obtained directly through questionnaires. Sampling using sensus sampling methods and methods of analysis used in this research was the path analysis. Â Based on the research results revealed that organizational communication, and service culture have effect on service behavior. And variable service behavior have effect of the firm competitive advantage. Â